Bionic traditional Chinese medicine co-assembled drug delivery system for targeting myocardial fibrosis and application of bionic traditional Chinese medicine co-assembled drug delivery system
Through the co-assembly of the drug delivery system of bionic Chinese medicine, the nanoparticles formed by co-assembly of LS102 and LIG are modified through platelet membranes to achieve targeted delivery of myocardial fibrosis, solving the problem that drugs in the prior art are difficult to target myocardial fibrosis, and achieving efficient and safe therapeutic effects.
Patent Information
- Application Number
- CN202411689934.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-02-28
AI Technical Summary
The prior art is difficult to effectively target and treat myocardial fibrosis, resulting in poor drug efficacy and causing systemic toxic side effects.
The drug delivery system PV@LNP is co-assembled by bionic Chinese medicine. The nanoparticle LNP formed by co-assembled astragalus metronidine derivative LS102 and Z-oxyprolactone LIG is prepared by platelet membrane modification to achieve targeted delivery of myocardial fibrosis site.
The PV@LNP system can effectively target myocardial damage blood vessels, improve myocardial fibrosis symptoms, restore cardiac function, and is highly safe and efficient.
Smart Images

Figure CN119524000A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a drug delivery system, in particular to a bionic traditional Chinese medicine co-assembly drug delivery system targeting myocardial fibrosis and application thereof. Background Art
[0002] Cardiovascular disease (CVD) has become the leading cause of death worldwide. According to WHO data, cardiovascular disease accounts for 31% of deaths among the population who died of the disease. Myocardial fibrosis (MF) is characterized by excessive production and deposition of scar tissue. It is involved in the occurrence and development of various cardiovascular diseases such as hypertension, myocardial infarction and heart failure. Myofibroblasts play a key role in promoting excessive deposition of extracellular matrix and tissue remodeling. Although conventional CVD treatments can relieve clinical symptoms, there are no effective drugs to reverse myocardial fibrosis in clinical practice due to the many factors that cause myocardial fibrosis and unclear mechanisms. Therefore, conducting research on the prevention and treatment of myocardial fibrosis and reducing cardiovascular mortality are important scientific issues related to national health and public health.
[0003] Danggui Buxue Decoction is composed of the herbal medicine pair of Astragalus and Angelica, and is known as a classic prescription for the treatment of cardiovascular diseases. Astragaloside derivative LS102 is a new natural compound obtained by replacing the alcohol hydroxyl group on astragaloside with a carboxyl group. The molecular formula is C 41 H 66 O 15 (Reference: https: / / doi.org / 10.1016 / j.phymed.2018.09.019). In previous studies, it was confirmed that the astragaloside derivative LS102 has significant myocardial protective effects. Z-ligustilide (LIG, molecular formula C 12 H 14 O 2 ) is a representative small molecule isolated from Angelica sinensis, and it has also been reported to protect vascular endothelial cells from oxidative stress and inhibit inflammation and fibrosis. Therefore, the combined use of LS102 and Z-ligustilide (LIG) has great potential in the treatment of myocardial fibrosis, but there are no reports on the efficacy of LS102 and LIG as a pharmaceutical composition and their co-assembled nanoparticles.
[0004] Given the special pathological background of myocardial fibrosis, it is ideal that the drug delivery system targets and actively accumulates in the fibrotic site, thereby improving the targeted efficacy. In order to overcome the limitation of nanoparticles that trigger the clearance of the reticuloendothelial system after entering the bloodstream, biomimetic drug delivery systems have emerged. In particular, natural cell membranes, whose surface modification can prolong blood circulation time, mimic cell characteristics, enhance targeting, etc., can be used as protective carriers and functional elements. Platelets, as the smallest circulating blood cells, can be naturally recruited to the damaged endothelium, thereby acquiring intrinsic affinity for the damaged heart. In addition, platelet membranes, as anucleated cells, are easier to extract. The membrane proteins CD62p, CD47, and CD41 expressed on the surface of platelets give nanoparticles valuable biological properties, including escaping the clearance of the reticuloendothelial system and achieving specific targeting of the damaged endothelium. At present, the application of biomimetic Chinese medicine self-assembly drug delivery systems constructed based on platelet membranes in myocardial fibrosis still needs further exploration.
[0005] Summary of the invention
[0006] In view of the deficiencies of the prior art, the present invention provides a new application of a bionic Chinese medicine co-assembly drug delivery system targeting myocardial fibrosis, which effectively solves the problems mentioned in the above background technology.
[0007] In order to solve the above problems, the technical solution adopted by the present invention is:
[0008] A use of a traditional Chinese medicine composition in the preparation of a drug for treating myocardial fibrosis, characterized in that the traditional Chinese medicine composition is composed of an astragaloside derivative LS102 and Z-ligustilide LIG;
[0009]
[0010] The application is characterized in that the traditional Chinese medicine composition is nanoparticles LNP formed by co-assembly of LS102 and LIG.
[0011] The application is characterized in that the nanoparticles LNP are prepared by the following steps: the molar ratio of LS102 to LIG is between 1:1-1:4, the concentration of LS102 is in the range of 0.5-1.5 mg / mL, and the concentration of LIG is in the range of 0.25-1 mg / mL. After complete dissolution, they are added dropwise into the aqueous phase, placed in a magnetic stirrer and stirred at a speed of 500-1000 rpm for 5-10 minutes, and then transferred to a dialysis bag for dialysis for 24-36 hours to obtain the nanoparticles LNP.
[0012] A bionic Chinese medicine self-assembled nano drug delivery system PV@LNP is used in the preparation of drugs for treating myocardial fibrosis, wherein PV@LNP is prepared from platelet membrane PV-modified nanoparticles LNP.
[0013] The application is characterized in that the PV@LNP is prepared by encapsulating nanoparticles LNP after platelet membrane is ultrasonically dispersed, wherein the ultrasonic power is 100-300W and the time is 5-20min.
[0014] The application is characterized in that the PV@LNP is prepared by the following steps: PV solution and LNP solution are mixed in a ratio of 100-200 μg PV total protein mass: 200-400 μg LNP.
[0015] Beneficial Effects
[0016] Myocardial fibrosis is a remodeling process of the cardiac interstitium, characterized by abnormal proliferation of cardiac interstitial fibroblasts in myocardial tissue, excessive accumulation of collagen fibers, significant increase in collagen concentration and volume fraction per unit mass of myocardium, imbalance in the proportion of various types of collagen and abnormal distribution. Some common cardiovascular diseases in clinical practice have different degrees of myocardial fibrosis, such as diabetic cardiomyopathy, viral myocarditis, ischemic cardiomyopathy, hypertensive heart disease, and myocardial infarction. In particular, myocardial infarction has a high incidence and mortality rate worldwide. After myocardial infarction, a large number of cardiac fibroblasts are strongly activated and secrete extracellular matrix to form fibrotic tissue to replace damaged myocardial tissue, leading to ventricular remodeling and further decline in cardiac function, and eventually developing into end-stage heart failure. At present, there is no effective treatment to prevent pathological fibrosis caused by myocardial infarction. Due to the inability to specifically target and deliver to the damaged fibrotic area, most drug trials fail to achieve the expected results and cause systemic toxic side effects. Therefore, developing a drug delivery system that can directly target the site of fibrosis with high safety and efficiency is a major challenge that needs to be addressed in the field of cardiovascular medicine (https: / / pubs.acs.org / doi / 10.1021 / acsnano.2c10042).
[0017] The present invention first confirmed that astragaloside derivatives (LS102) and ligustilide (LIG) formed a pharmaceutical composition nanoparticle LNP to produce a synergistic effect and effectively improve myocardial fibrosis, and its efficacy is better than that of LS102 or LIG alone, while the use of LS102 or LIG alone did not show improvement in myocardial fibrosis or the improvement was limited. It was further found that the bionic Chinese medicine co-assembled drug delivery system (PV@LNP) has better efficacy than LNP.
[0018] As for LNP: The inventors surprisingly found that LS102 and LIG can be assembled into spherical nanoparticles LNP without additional additives such as surfactants. Figure 8As shown, the co-assembled LNP has the common characteristics of parallel plane stacking of intermolecular spatial configuration and close proximity of hydrophilic ends, which is conducive to the hydrogen bonding near the hydrophilic surface, mainly including hydrophobic interaction and hydrogen bonding, and the above-mentioned interaction forms nanoparticles. The platelet membrane PV is further modified on the surface of LNP to obtain a bionic Chinese medicine co-assembled drug delivery system (PV@LNP), and the efficacy of the PV@LNP is better than that of LNP. The reason is that after intravenous injection of the system, on the one hand, because the CD47 protein of the platelet membrane is retained on its surface, it can escape the recognition of immune cells, prolong the circulation in the body, and passively target to the site of myocardial fibrosis. On the other hand, the membrane protein CD62P binds to the PSGL-1 ligand on the surface of injured blood vessels in the site of myocardial fibrosis, respectively, to achieve precise active targeted delivery, showing great therapeutic potential in myocardial fibrosis. At present, there are no reports on bionic Chinese medicine co-assembled drug delivery systems containing the above two effective ingredients of Chinese medicine.
[0019] Further: Screening the effect of different molar ratios of LS102 and LIG on the co-assembly process, it was found that LS102 monomers could not assemble into nanoparticles. LS102 and LIG were mixed at molar ratios of 1:1, 1:2, and 1:4. When the molar ratio of LNP was 1:2, a stable, uniform appearance and a clear Tyndall effect were formed, but when the LIG content was further increased, the resulting solution became turbid and showed a weak Tyndall effect.
[0020] In summary, the platelet membrane is modified on the LNP surface by ultrasonic dispersion technology to construct a bionic Chinese medicine co-assembly drug delivery system, which has strong stability, effectively targets myocardial damaged blood vessels, improves myocardial fibrosis symptoms, and restores heart function. A bionic Chinese medicine co-assembly nano drug delivery system screened by the present invention has outstanding substantial characteristics, the best practical effect, and has great application prospects in the treatment of diseases such as myocardial fibrosis, myocardial infarction, atherosclerosis and hypertension. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 The Tyndall effect of the co-assembled nanoparticles LNPs at different molar ratios in the present invention;
[0022] Figure 2 This is a particle size distribution diagram of the co-assembled nanoparticles LNP in the present invention;
[0023] Figure 3 This is a potential diagram of the co-assembled nanoparticles LNP in the present invention;
[0024] Figure 4 This is a transmission electron microscopy image of the co-assembled nanoparticles LNP of the present invention;
[0025] Figure 5 Fourier transform infrared spectroscopy analysis of the co-assembled nanoparticles LNP in the present invention;
[0026] Figure 6 X-ray diffraction analysis of the co-assembled nanoparticles LNP in the present invention;
[0027] Figure 7 This is a molecular dynamics simulation diagram of the co-assembled nanoparticles LNP of the present invention;
[0028] Figure 8 It is a molecular interaction diagram of the co-assembled nanoparticles LNP in the present invention;
[0029] Fig. 9 This is the particle size distribution diagram of the bionic Chinese medicine co-assembled drug delivery system PV@LNP in the present invention;
[0030] Fig.10 This is a transmission electron microscopy image of the bionic Chinese medicine co-assembled drug delivery system PV@LNP of the present invention;
[0031] Fig.11 The stability of the bionic Chinese medicine co-assembled drug delivery system PV@LNP in the present invention;
[0032] Fig.12 The cytotoxicity of the biomimetic Chinese medicine co-assembled drug delivery system PV@LNP in the present invention;
[0033] Fig.13 This is to investigate the targeting of the bionic Chinese medicine co-assembled drug delivery system PV@LNP in the present invention;
[0034] Fig.14 This is a cardiac ultrasound analysis diagram of the pharmacodynamics of the bionic Chinese medicine co-assembled drug delivery system PV@LNP of the present invention;
[0035] Fig.15 This is the pharmacodynamics Masson staining diagram of the bionic Chinese medicine co-assembled drug delivery system PV@LNP of the present invention;
[0036] Fig.16 This is the pharmacodynamic Sirius red staining image of the bionic Chinese medicine co-assembled drug delivery system PV@LNP of the present invention;
[0037] Fig.17 This is the HE staining diagram of the pharmacological effects of the co-assembled nanoparticles LNP, LS102, and LIG in the present invention. DETAILED DESCRIPTION
[0038] The following are specific embodiments of the present invention, and the technical solutions of the present invention are further described in conjunction with the accompanying drawings, but the present invention is not limited to these embodiments.
[0039] Example 1 Preparation method of a bionic Chinese medicine co-assembly drug delivery system targeting myocardial fibrosis
[0040] 1. Prescription screening of co-assembled nanoparticles LNP
[0041] Taking LS102 and LIG as the research objects, the effects of different molar ratios of LS102 and LIG on the co-assembly process were investigated. The specific preparation steps were as follows: a certain amount of LS102 and LIG were weighed according to the molar ratio of LS102 to LIG of 1:1, 1:2, and 1:4, 1 mL of anhydrous ethanol was added to dissolve completely, and then dropped into 10 mL of ultrapure water under vigorous stirring, and stirred at 1000 rpm for 10 min. After that, the resulting solution was dialyzed for 48 hours with a dialysis bag to remove organic solvents and unassembled drugs. The Tyndall effect of LIG, LS102, LNP 1:1, LNP 1:2, and LNP 1:4 solutions was observed by laser pen irradiation. 3 mL of sample was placed in a particle size analyzer to determine the particle size, polydispersity coefficient, and potential. Finally, LNP was freeze-dried by a freeze dryer and stored at 4 °C.
[0042] Results: In aqueous solution, LS102 monomers were difficult to self-assemble into nanoparticles, showing a weak Tyndall effect ( Figure 1 ). Three LNP solutions were prepared with LS102 and LIG at molar ratios of 1:1, 1:2, and 1:4, named LNP 1:1, LNP 1:2, and LNP 1:4, respectively. The results showed that a stable, uniform appearance and a clear LNP Tyndall effect were formed at a molar ratio of 1:2. However, after further increasing the LIG content, the resulting solution became turbid, showing a weakened Tyndall effect.
[0043] Furthermore, according to the particle size analyzer analysis, LNPs with different LS102 and LIG molar ratios showed similar particle sizes of about 190-200 nm. However, LNP 1:2 had the narrowest particle size distribution compared to LNP 1:1 and LNP 1:4, indicating a more uniform distribution ( Figure 2 Among the co-assembled nanoparticles, LNP 1:2 also exhibited a ζ potential of -30 mV, indicating the highest stability, which is consistent with the obvious Tyndall phenomenon ( Figure 3 ).
[0044] 2. Characterization of the microscopic morphology of co-assembled nanoparticles LNP
[0045] An appropriate amount of LNP solution was placed on a copper mesh, dried, and the particle morphology was observed under a high-resolution transmission electron microscope.
[0046] Results: The morphological differences among LIG, LNP 1:1, LNP 1:2, and LNP 1:4 were observed under transmission electron microscopy. Figure 4As shown in the figure, the self-assembled LIG monomer is nearly spherical. Meanwhile, the shape of LNP 1:2 is the most uniform and best. In contrast, increasing or decreasing the percentage of LS102 shows unsatisfactory morphology and particle size. Therefore, there are obvious morphological differences between LS102 and LIG at different molar ratios, which may be due to the interaction that changes the microscopic morphology of the co-assembled nanoparticles LNP.
[0047] 3. Fourier infrared spectroscopy analysis of co-assembled nanoparticles LNP
[0048] Take an appropriate amount of co-assembled nanoparticles LNP freeze-dried powder and press it together with potassium bromide, and scan it with a Fourier infrared spectrometer in the wavelength range of 4000-500cm -1 Scan to obtain a spectrum.
[0049] Results: See Figure 5 , Fourier transform infrared spectroscopy data showed that LS102 has a peak at 3362 cm -1 The typical stretching vibration of OH group is shown at 1760 cm -1 The C=O group is shown at 1044 cm -1 The peaks at 3376 cm and 102 cm respectively correspond to the CO groups in the glucuronic acid of LS102. -1 )、LNP 1:2(3382cm -1 ) and LNP 1:4 (3381cm -1 ). Therefore, the IR results indicate that there is a hydrogen bonding interaction between LS102 and LIG driving the co-assembly process.
[0050] 4. X-ray diffraction analysis of co-assembled nanoparticles LNP
[0051] An appropriate amount of co-assembled nanoparticle LNP freeze-dried powder was tested on an X-ray diffractometer at 40 kV and 40 mA, using Cu-Kα radiation at room temperature, and the 2θ diffraction angle range was 5°-80°.
[0052] Results: See Figure 6 LS102 shows strong and sharp diffraction peaks at 4-20°, indicating its crystalline structure. Interestingly, some characteristic crystalline peaks of LS102 were also observed in LNP 1:1, but completely disappeared in LNP 1:2 and replaced by a larger broad peak at 18.24°, indicating an amorphous structure after co-assembly. This means that the hydrophobic interaction between LS102 and LIG drives the co-assembly.
[0053] 5. Molecular dynamics simulation of co-assembled nanoparticles LNP
[0054] Molecular dynamics (MD) simulations were performed using GROMACS2021.4 software. A 10nm×10nm×10nm simulation box consisting of 20 LS102 and 40 LIG molecules was constructed. The steepest descent method was used to eliminate unreasonable contacts between atoms in the simulation box and minimize the energy. The simulation chamber was completely released when the maximum force of the system was less than 10kJ / (mol·nm). Then, a sampling simulation of 300ns was performed at 298.15K using a V-type rescaling thermostat, and the temperature time constant was set to 2ps. Hydrogen bonds were calculated using the LINCS algorithm with an integration step of 2fs. Electrostatic interactions were calculated using the particle mesh Ewald method. During the MD simulation, the conformation was saved every 10ps, and the visualization of the simulation results was completed using the Gromacs embedding program and VMD.
[0055] Results: Figure 7 As shown, the dynamic co-assembly process of the LNP system was recorded at 0, 50, 100, 150, 200 and 300 ns, respectively. Thereafter, the LS102 molecules and the LIG molecules were still in a dispersed state at 0 ns and were completely aggregated at 300 ns. In addition, the increase in the number of hydrophobic interactions and intermolecular hydrogen bonds between LS102 and LIG promoted the co-assembly process. The carboxyl group of LS102 forms hydrogen bonds with the carbonyl group of LIG. MD simulations show that the co-assembled LNPs have the common characteristics of parallel planar stacking of the intermolecular spatial configuration and the close proximity of the hydrophilic ends, which facilitates the hydrogen bonding near the hydrophilic surface ( Figure 8 ). This also means that hydrogen bonding interactions and hydrophobic interactions are the main driving forces for co-assembly, which is consistent with Fourier transform infrared spectroscopy.
[0056] 6. Preparation method of biomimetic Chinese medicine co-assembly drug delivery system PV@LNP
[0057] Platelets were obtained from fresh rat blood and platelet vesicles PV were obtained after repeated freezing and thawing at -80°C and room temperature. PV solution and LNP solution were mixed at a ratio of (100-200) μg PV (total protein mass): (200-400) μg LNP, sonicated for 10 min in an ice bath, and then extruded 5 times using a 200 nm microporous filter to obtain uniform size. Excess PV was centrifuged at 5000 g for 10 min. DiD-labeled PV@LNP was prepared by adding 50 μM DiD.
[0058] Results: See Fig. 9, the particle size of PV@LNP was 198.74±0.58nm, and the polydispersity coefficient was 0.148±0.02, showing a smaller particle size distribution and particle size than PV (222.08±4.28nm, polydispersity coefficient was 0.238±0.02). In addition, the potential of PV@LNP was almost the same as that of PV, indicating the successful modification of PV.
[0059] 7. Microscopic morphology characterization of biomimetic Chinese medicine co-assembled drug delivery system PV@LNP
[0060] An appropriate amount of PV@LNP solution was placed on a copper mesh, dried, and the particle morphology was observed under a high-resolution transmission electron microscope.
[0061] Results: See Fig.10 PV@LNP showed an obvious core-shell structure, which further demonstrated the successful modification of PV. The particle size distribution was 180-190nm, which was consistent with the results of particle size analysis.
[0062] 8. Stability of the biomimetic Chinese medicine co-assembled drug delivery system PV@LNP
[0063] 3 mL of freshly prepared LNP and PV@LNP solutions were placed in phosphate buffer containing 10% fetal bovine serum. The particle size and polydispersity coefficient of the samples were measured using a particle size analyzer at 0, 12, 24, 36, and 48 h after placement to investigate the stability.
[0064] Results: See Fig.11 PV@LNP maintained its dimensional stability well, while the particle size and PDI of LNP increased significantly. This phenomenon was attributed to the increase in blood compatibility after PV coating, which contributed to the stability of the nanoparticles in a simulated plasma environment in vitro.
[0065] 9. Cytotoxicity of PV@LNP, a biomimetic Chinese medicine co-assembly drug delivery system
[0066] H9C2 cells were cultured in DMEM medium containing 10% fetal bovine serum at 37°C and 5% CO2. HUVECs in the logarithmic growth phase were evenly inoculated into 96-well plates and cultured for 24 hours. 100 μL of LNP or PV@LNP solution was added to each well and cultured for 48 hours. The CCK-8 method was used to detect the cell viability of HUVECs, and the absorbance was measured at 490 nm using a multifunctional microplate reader to calculate the cell viability.
[0067] Results: See Fig.12 ,As we expected, H9C2 cells treated with different concentrations of nanoparticles, PV@LNP showed a cell viability of more than 90% with no obvious toxicity.
[0068] 10. Targeting investigation of biomimetic Chinese medicine co-assembled drug delivery system PV@LNP
[0069] Myocardial fibrosis (MF) model was established by subcutaneous injection of isoproterenol (50 mg / kg / d) in C57BL / 6J mice for 14 days. DiD was then released and DiD-PV@LNP was intravenously injected into MF mice to evaluate the biodistribution of the nanoparticles. Fluorescence intensity was analyzed under an in vivo imaging system at 1, 2, 4, 8, 12, and 24 hours after administration.
[0070] Results: After nanoparticle production and characterization, the feasibility of intravenous delivery of LNPs was systematically investigated to ensure effective accumulation of LNPs in the myocardial tissue of MF mice. To this end, DiD-labeled PV@LNPs were prepared. After injection, MF mice were photographed by an in vivo imaging system at 1, 2, 4, 8, 12, and 24 hours ( Fig.13 ). To verify the accumulation of nanoparticles in the myocardium, major organs were collected 24 hours after injection. Compared with free DiD, PV@LNP-injected hearts showed greater fluorescence accumulation, which may be due to the role of PV in targeting damaged myocardium. Notably, fluorescence distribution was also observed in organs such as the liver and spleen due to the metabolism of nanoparticles by these organs after administration, which is consistent with previous studies.
[0071] 11. Pharmacodynamic evaluation of biomimetic Chinese medicine co-assembly drug delivery system PV@LNP in the treatment of myocardial fibrosis
[0072] The mice were randomly divided into a normal group, a model group, a LNP group, and a PV@LNP group. The mice in the model group, the LNP group, and the PV@LNP group were subcutaneously injected with isoproterenol, while the mice in the normal group were injected with the same volume of saline. At the same time, the mice in the LNP group and the PV@LNP group were intraperitoneally injected with the corresponding nanoparticles containing 20 mg / kg LS102 and 10 mg / kg LIG. After 14 days of administration, the mice were anesthetized with isoflurane. Then, echocardiography was performed on an ultra-high-resolution small animal ultrasound imaging machine to evaluate the recovery of cardiac function.
[0073] Results: MF mice that received different nanoparticles treatments via intravenous injection for 14 days were monitored by echocardiography. As shown in Figure 14, mice given isoproterenol showed significant functional changes compared to normal mice, implying the successful establishment of the MF model. Cardiac function-related indices of mice were significantly restored after treatment with different nanoparticles. In particular, PV@LNP almost recovered to the level of healthy mice compared to mice treated with other tested nanoparticles, which was mainly due to the effective delivery of LNPs to the damaged myocardium. Therefore, this finding confirms the expected effect of intravenous platelet membrane-TCM co-assembled nanodelivery system in restoring cardiac function in MF mice, representing a potential therapeutic modality for the clinical treatment of MF.
[0074] 12. Masson staining of biomimetic Chinese medicine co-assembly drug delivery system PV@LNP for the treatment of myocardial fibrosis
[0075] The heart tissue sections were sequentially dewaxed into water, incubated with potassium dichloride overnight, and heated at 63 °C for 1 h. Next, the sections were stained with a fuchsin solution for 10 min. After a slight rinse with distilled water, the sections were treated with a phosphomolybdic acid solution for 2s-2min until the collagen fibers faded, and then stained with aniline blue for 2min to recolor the collagen fibers. Finally, the sections were dehydrated with graded alcohols, cleared with toluene, and sealed with neutral glue. Representative images of the sections were collected using a digital slide scanner.
[0076] Results: The changes of collagen fiber deposition in mouse hearts were studied by Masson staining. Fig.15 , consistent with the deterioration of cardiac function, isoproterenol stimulation significantly increased the severity of fibrosis in mice, and nanoparticle treatment alleviated the symptoms to some extent, especially PV@LNP treatment.
[0077] 13. Sirius red staining of biomimetic Chinese medicine co-assembly drug delivery system PV@LNP for the treatment of myocardial fibrosis
[0078] The heart tissue was decalcified, dehydrated, embedded, and sliced in 10% EDTA. Next, the heart tissue sections were dewaxed into water and stained with hematoxylin. After drying, the sections were stained with Sirius red dye complex solution for 5-10 minutes and dehydrated with n-butanol for 5 minutes. Finally, the sections were dehydrated with graded ethanol, cleared with toluene, and sealed with neutral glue. Representative images of the sections were collected using a digital slide scanner.
[0079] Results: See Fig.16 , type I collagen can reflect the passive expansion capacity of collagen fibers in scar tissue. In this work, I used Sirius red staining to visualize collagen. Similarly, the results of Sirius red staining also showed that extensive type I collagen was observed in the hearts of LNP-treated mice. However, the mice treated with PV@LNP had less collagen. The above evidence suggests that PV@LNP restored heart function despite reducing collagen deposition and scar tissue.
[0080] 14. HE staining of co-assembled nanoparticles LNP for the treatment of myocardial fibrosis
[0081] After 14 days of treatment, the isolated heart tissues were fixed with polyformaldehyde, dehydrated, embedded, and sliced in sequence. Then, the heart slices were dewaxed into water in sequence, stained with hematoxylin for 5-10 minutes, differentiated with hydrochloric acid alcohol solution for 3 seconds, restored to blue with weak alkaline aqueous solution, stained with eosin for 3 minutes, dehydrated with gradient alcohol, transparent with toluene, and sealed with neutral glue. Finally, representative images of the slices were captured by a digital slice scanner.
[0082] Results: See Fig.17 , HE staining reflects myocardial damage in mice. The cardiomyocytes in the normal group were uniformly red, tightly arranged, clearly visible, and uniform in size. In the model group, consistent with the deterioration of cardiac function, a large amount of fibrous tissue hyperplasia appeared in the myocardium, and the cardiomyocytes were loosely arranged and of different sizes, indicating obvious damage. The myocardial tissue of mice treated with LS102 or LIG alone still had a certain amount of pathological fibrosis, showing limited anti-myocardial fibrosis efficacy. Compared with single-drug treatment, the hypertrophy of cardiomyocytes gradually recovered after LNP treatment, and the arrangement of cardiomyocytes was more orderly and clear, indicating that the combined application of LS102 and LIG is more effective than that of single drugs.
Claims
1. Use of a Chinese medicine composition in the preparation of a drug for treating myocardial fibrosis, characterized in that: The traditional Chinese medicine composition is composed of astragaloside derivative LS102 and Z-ligustilide LIG; Astragaloside derivative LS102 Z-ligustilide LIG.
2. The use according to claim 1, characterized in that: The traditional Chinese medicine composition is nanoparticles LNP formed by co-assembly of LS102 and LIG.
3. The use according to claim 2, characterized in that: The nanoparticles LNP are prepared by the following steps: the molar ratio of LS102 to LIG is between 1:1-1:4, the concentration of LS102 is in the range of 0.5-1.5 mg / mL, and the concentration of LIG is in the range of 0.25-1 mg / mL. After complete dissolution, they are added dropwise into the aqueous phase, placed in a magnetic stirrer and stirred at a speed of 500-1000 rpm for 5-10 minutes, and then transferred to a dialysis bag for dialysis for 24-36 hours to obtain the nanoparticles LNP.
4. Application of a bionic Chinese medicine co-assembled drug delivery system PV@LNP in the preparation of drugs for treating myocardial fibrosis, characterized in that: PV@LNP is prepared by modifying the nanoparticles LNP described in claim 2 or 3 by platelet membrane PV.
5. The use according to claim 4, characterized in that: The PV@LNP is prepared by encapsulating nanoparticles LNP after platelet membrane PV is dispersed by ultrasound, wherein the ultrasound power is 100-300W and the time is 5-20min.
6. The use according to claim 5, characterized in that: The PV@LNP is prepared by the following steps: PV solution and LNP solution are mixed in a ratio of 100-200 μg PV total protein mass: 200-400 μg LNP.